Communication and cognition - LaPointe, Leonard L.; Stierwalt, Julie; Purdy, Mary H. (Aphasia and related neurogenic language disorders, 2018)
Rapid advances in neural imaging, particularly in regard to neural plasticity and brain changes, have resulted in an evolving neurorehabilitation paradigm for aphasia and related language disorders. Aphasia and Related Neurogenic Language Disorders has been adopted worldwide as a text for aphasia courses. This new 5th edition by Leonard LaPointe and Julie Stierwalt encompasses state-of-the-art concepts and approaches from an impressive cadre of experts who work in research labs, classrooms, clinics, and hospitals-including the world-renowned Mayo Clinic.As in previous editions, this book embraces a humanistic approach to treatment, addressing multicultural and multilinguistic considerations and social model interventions. The text encompasses a full continuum of cognitive-language disorder management-from everyday practicalities, assessment, and treatment to disorder-specific cases with evidence-based data. Additions to the 5th edition include chapters on pragmatics and discourse, telepractice, digital and electronic advances, funding and reimbursement, and comprehension, syntax, and linguistic based disorders.Key Features:A new chapter on neuroanatomical basics features exquisite illustrationsAn in-depth look at neurogenic communication disorders from Mayo Clinic provides firsthand insights on treating patients in an acute care hospital settingDiscussion and test questions, case studies, and clinical pearls offer invaluable didactic guidanceA chapter on expanded traumatic brain injury covers blast injuries and multisystem injuriesThis is the most comprehensive yet concise resource on aphasia and related disorders available today. New legions of speech language pathology students, residents, course directors, and practitioners will discover a remarkable guide on the treatment of communication disorders.
Keywords: dept.cmd